136 APOLIPOPROTEIN E GENOTYPE FREQUENCIES IN A PROSPECTIVE STUDY OF SPORADIC LATE -ONSET DEMENTIA. Issue 1 (1st January 2007) - Hong, S.; Mueller, C.; Magaki, S.; Petersen, F.; Kirsch, W. M.
Abstract : Background and Significance: The correlation of apolipoprotein E (ApoE) genotype frequencies with the development of sporadic progressive late-onset dementia has been demonstrated in several studies. In particular, the risk effect of the ApoE 4 allele in the development of Alzheimer's disease (AD) has been well documented. Over the past 4 years we have studied a cohort of 76 patients with mild cognitive impairment (MCI) and 28 controls and followed the cognitive course of these cases with serial psychometric examinations and MRI sequences that include susceptibility weighted imaging (SWI) to determine iron content. Serial blood samples have been collected for multiple systems of analysis, and this report deals with the analysis of patient DNA for identification of ApoE genotype. The aim of this study is to correlate the identified ApoE allelic frequencies in these cases with progression from MCI to mild AD. Methods: The subjects consist of a community-based cohort of 76 MCI and 28 cognitively normal participants studied with IRB approval. Classifications of MCI were based on the Mayo Clinic rating criteria, and all cases had psychometric examinations to diagnose them as normal, MCI, and progressive MCI (PMCI) or AD. Patient DNA was extracted using standard techniques and the 270 bp polymorphic region of ApoE was amplified by PCR with primers that have previously been used. The DNA digestion was carried out with HhaI endonucleases and the resulting samples were visualized on both 4% agarose and 0.8% acrylamide gels for identification of the three different isoforms of ApoE. Results and Conclusions: The frequency of the genotypes for ApoE 2, 3, and 4 for the normal control population were 4.1% E2, 77.1% E3, and 14.5% E4. The stable MCI population frequencies were 9.1% E2, 75% E3, and 15.9% E4. However, the frequencies for the PMCI group were 0% E2, 75% E3, and 25% E4. These results confirm the role of ApoE 4 as a risk factor for AD. In addition, it appears that the ApoE 2 allele may be protective against the development of dementia. We are in the process now of doing additional studies to assess the relevance of patient genotypes to developing AD and brain microhemorrhages as indicated by SWI studies.